Default, Currency Crises, and Sovereign Credit Ratings - Reinhart, Carmen M. (Washington, DC: World Bank, 2014)
Sovereign credit ratings play an important part in determining countries' access to international capital markets and the terms of that access. In principle, there is no reason to expect that sovereign credit ratings should systematically predict currency crises. In practice, in emerging market economies there is a strong link between currency crises and default. Hence if credit ratings are forward-looking and currency crises in emerging market economies are linked to defaults, it follows that downgrades in credit ratings should systematically precede currency crises. This article presents results suggesting that sovereign credit ratings systematically fail to predict currency crises but do considerably better in predicting defaults. Downgrades in credit ratings usually follow currency crises, possibly suggesting that currency instability increases the risk of default.